Synthesis, Spectroscopy, Thermal Analysis, Electrochemistry and Superoxide Scavenging Activity of a New Bimetallic Copper(II) Complex - Babita Sarma; Diganta Kumar Das (Journal of Chemistry)
A new bimetallic copper(II) complex has been synthesized with ligand obtained by the condensation of salicylaldehyde and the amine derived from reduction of nitration product of benzil. The ligand was characterized by 1H NMR and mass spectra, and the binuclear Copper(II) complex was characterized by vibrational and electronic spectra, EPR spectra, and magnetic moment measurement. Thermogravimetric analysis study and electrochemical study of the complex were also done. The complex was found to show superoxide dismutase activity.